2004
DOI: 10.1016/j.ejheart.2003.10.007
|View full text |Cite
|
Sign up to set email alerts
|

Suppression of cytokines and nitric oxide production, and protection against lethal endotoxemia and viral myocarditis by a new NF‐κB inhibitor

Abstract: These findings suggest that the activation of NF-kappaB plays an important role in the pathogenesis of endotoxemia and viral myocarditis, and that the NF-kappaB inhibitor, SUN C8079, may be therapeutic in these disorders.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
32
0
2

Year Published

2006
2006
2023
2023

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 42 publications
(43 citation statements)
references
References 34 publications
3
32
0
2
Order By: Relevance
“…NF-κB inhibitor suppressed the expressions of cardiac TNF-α in vivo and vitro and prevented the development of myocarditis [30]. It was also reported that adiponectin reduced the activation of NF-κB [31]. The AT1-receptor blocker significantly attenuated expression of TNF-α and activation of NF-κB [8].…”
Section: Discussionmentioning
confidence: 91%
“…NF-κB inhibitor suppressed the expressions of cardiac TNF-α in vivo and vitro and prevented the development of myocarditis [30]. It was also reported that adiponectin reduced the activation of NF-κB [31]. The AT1-receptor blocker significantly attenuated expression of TNF-α and activation of NF-κB [8].…”
Section: Discussionmentioning
confidence: 91%
“…The mechanism by which honey inhibits both pro-inflammatory cytokines (such as TNF-α and IL-1β), and NO is unclear, but it may involve the inhibition of NF-κB. A previous study shows that NF-κB prevents the release pro-inflammatory cytokines and inhibits the release of iNOS [27,28]. However, the inhibitory effect of honey on the anti-inflammatory cytokine, IL-10, remains a matter for speculation.…”
Section: Discussionmentioning
confidence: 96%
“…We have previously reported that pimobendan, a phosphodiesterase inhibitor, protects against viral myocarditis through its inhibition of NF-kB activation (17,18). We have also recently found that NF-kB inhibitor prevents the development of EMCV myocarditis and inhibits the expression of proinflammatory cytokines in cardiac tissues (19).…”
mentioning
confidence: 98%